2006
DOI: 10.1117/12.653295
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the dental pulp using optical coherence tomography

Abstract: The inner structure of teeth, i.e. the root canal anatomy, is very complex. However a good knowledge of endodontic architecture is the first step towards successful endodontic treatment. Optical coherence tomography (OCT) is a powerful technique to generate images of hard and soft tissue. Its images show dependency on the optical properties of the tissue under analysis. Changes in the scattering and absorption of tissues can be observed through the OCT images. In this work, we used optical coherence tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…OCT in dentistry has been recently used to in vitro studies evaluating enamel interface restoration [21], early caries diagnostics [22], and analysis of the performance of dental materials [23]. In 2006, the first OCT image of dental pulp was performed using rat's teeth [24], and more recently, remaining dentin and pulp chamber from human's teeth were also imaged by OCT in vitro [25].…”
Section: Introductionmentioning
confidence: 99%
“…OCT in dentistry has been recently used to in vitro studies evaluating enamel interface restoration [21], early caries diagnostics [22], and analysis of the performance of dental materials [23]. In 2006, the first OCT image of dental pulp was performed using rat's teeth [24], and more recently, remaining dentin and pulp chamber from human's teeth were also imaged by OCT in vitro [25].…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, Kauffman et al performed the first OCT image of dental pulps using rat's teeth. 19 The key elements of an OCT setup include a broadband light source, whose spectral width limits the axial spatial resolution; an interferometer, which generally employs a Michelson design containing in one of the arms the sample and in the other arm a delay line; and an optical detector, whose signal output is electronically treated and fed to a computer for the image generation. Two domains can be exploited for implementation of an OCT system: the time domain or the spectral domain.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, early caries diagnostics (12) and the evaluation of enamel interface restoration (13) have been described. In 2006, Kauffman et al (14) reported the first OCT image of dental pulps using rat's teeth. Shemesh et al described the first OCT to characterize the root canals wall and diagnose vertical root fractures (15,16).…”
mentioning
confidence: 98%